Survey of Registered Nurses Working in the Metropolitan Hospitals on Bullying Experiences at Workplace in South Korea (Medico Legal Update, 2021)
This study aimed to identify the bullying experiences and coping patterns experienced by clinical nurses.A total of 215 nurses who had worked at 10 hospitals in Seoul from 3 September 2019 to 20 Octoberparticipated, but two of them had missing data. Ultimately, 213 subjects were included. The collecteddata were analyzed using the SPSS/WIN20.O program which were analyzed using the mean and standarddeviation. Subjects who experienced bullying accounted for 110 out of 213 (51.6%) in which 66.3% wereexperienced nurses and 21.8% were new nurses. To talk to a colleague was 57.3%, to work with a feeling ofhurt but remain calm was 56.4%, to forget by thinking about something else or doing something was 50%.The study on the coping response after bullying has not been revealed in previous Korean reports, and itis expected to be a useful information for preventing workplace bullying in the future and establishing animmediate and active coping system.